London's Urban Landscape Another Way of Telling - Tilley, Christopher (UCL Press, 2019)
London's Urban Landscape is the first major study of a global city to adopt a materialist perspective and stress the significance of place and the built environment to the urban landscape. Edited by Christopher Tilley, the volume is inspired by phenomenological thinking and presents fine-grained ethnographies of the practices of everyday life in London. In doing so, it charts a unique perspective on the city that integrates ethnographies of daily life with an analysis of material culture. The first part of the volume considers the residential sphere of urban life, discussing in detailed case studies ordinary residential streets, housing estates, suburbia and London's mobile 'linear village' of houseboats. The second part analyses the public sphere, including ethnographies of markets, a park, the social rhythms of a taxi rank, and graffiti and street art.